2008
DOI: 10.1021/jp807106h
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic Vibrational Spectroscopy Calculations for Proton-Bound Amino Acid Dimers

Abstract: Results of anharmonic frequency calculations carried out for GlysLysH(+) and GlyGlyH(+) are presented and compared to gas phase electrospray ionization (ESI) spectroscopy experiments. Anharmonic frequencies are obtained via correlation-corrected vibrational self-consistent field (CC-VSCF) calculations. The potential used is based on the PM3 semiempirical electronic structure method, but improved by fitting to ab initio MP2 calculations at the harmonic level. The key results are as follows: (1) Hydrogens acting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 61 publications
2
34
1
Order By: Relevance
“…143 It was found that the contribution is non-negligible, but not too significant to justify the increased cost of CPU time. While this approximation must be tested on a case by case basis, it has been applied extensively for many VSCF calculations of biological molecules 56,[144][145][146][147][148][149][150][151] with satisfactory results. The VSCF algorithm was introduced in the GAMESS 152 suit of program, and later also in the MOLPRO 153 program package.…”
Section: (B) Representation Of the Potentialmentioning
confidence: 99%
“…143 It was found that the contribution is non-negligible, but not too significant to justify the increased cost of CPU time. While this approximation must be tested on a case by case basis, it has been applied extensively for many VSCF calculations of biological molecules 56,[144][145][146][147][148][149][150][151] with satisfactory results. The VSCF algorithm was introduced in the GAMESS 152 suit of program, and later also in the MOLPRO 153 program package.…”
Section: (B) Representation Of the Potentialmentioning
confidence: 99%
“…15 Many successful anharmonic vibrational spectroscopy calculations based on VSCF method and its CC-VSCF variants have been reported, [13][14][15][16][17][18][19][20][21][22][23][24][25] even for molecules of considerable size (more than 10 atoms). 16,22 Nonetheless, it has been noted that PES computed on a grid derived from normal-mode displacement vectors expressed in rectilinear coordinates overestimates single-mode potentials and gives rise to artificially large mode-mode coupling potentials in the case of large amplitude vibrations, which, in turn, impedes the performance of VSCF method for such modes. 13,21 Considerable improvement in the soft mode description by the VSCF method has been achieved by using PES calculated on a grid obtained from normal-mode displacement vectors expanded in curvilinear (internal) coordinates, 23 which is devoid of factitious mode-mode coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The group of R.B. Gerber has in particular shown that PM3 representations can be accurate enough for vibrational spectroscopy of simple molecules [82] (static calculations). DFTB (DFT Tight Binding) also shows promising results for vibrational spectroscopy; see for instance [83][84][85][86][87].…”
Section: Many Good Reasons To Prefer Dynamical Anharmonic Spectroscopymentioning
confidence: 99%